The Uganda Newborn Study (UNEST): an effectiveness study on improving newborn health and survival in rural Uganda through a community-based intervention linked to health facilities - study protocol for a cluster randomized controlled trial - Waiswa, Peter; Peterson, Stefan S.; Namazzi, Gertrude; Kiracho Ekirapa, Elizabeth; Naikoba, Sarah; Byaruhanga, Romano; Kiguli, Juliet; Kallander, Karin; Tagoola, Abner; Nakakeeto, Margaret; Pariyo, George (Trials, 2012)
Reducing neonatal-related deaths is one of the major bottlenecks to achieving Millennium Development Goal 4. Studies in Asia and South America have shown that neonatal mortality can be reduced through community-based interventions, but these have not been adapted to scalable intervention packages for sub-Saharan Africa where the culture, health system and policy environment is different. In Uganda, health outcomes are poor for both mothers and newborn babies. Policy opportunities for neonatal health include the new national Health Sector Strategic Plan, which now prioritizes newborn health including use of a community model through Village Health Teams (VHT). The aim of the present study is to adapt, develop and cost an integrated maternal-newborn care package that links community and facility care, and to evaluate its effect on maternal and neonatal practices in order to inform policy and scale-up in Uganda. Methods/Design: Through formative research around evidence-based practices, and dialogue with policy and technical advisers, we constructed a home-based neonatal care package implemented by the responsible VHT member, effectively a Community Health Worker (CHW). This CHW was trained to identify pregnant women and make five home visits - two before and three just after birth - so that linkages will be made to facility care and targeted messages for home-care and care-seeking delivered. The project is improving care in health units to provide standardized care for the mother and the newborn in both intervention and comparison areas. The study is taking place in a new Demographic Surveillance Site in two rural districts, Iganga and Mayuge, in Uganda. It is a two-arm cluster randomized controlled design with 31 intervention and 32 control areas (villages). The comparison parishes receive the standard care already being provided by the district, but to the intervention villages are added a system for CHWs to visit the mother five times in her home during pregnancy and the neonatal period. Both areas benefit from a standardized strengthening of facility care for mothers and neonates.
Keywords: UNEST; Newborn; Community health workers; Uganda; Africa; Trial